Performance-Based Fire Safety in an Existing Residential Multi-Story Building in Surakarta - Wahyu Sujatmiko; Yulia Rahmawati; Ramadan Pratama Gumilar (Journal of Architectural Research and Design Studies, 2020)
Multi-story residential building for low-income communities, which is one of the vertical housing forms programmed by the current Indonesian government, must meet the requirements for the proper functioning of the building, including safety from fire hazards. Fulfillment of fire safety is carried out through three fire protection systems, namely: passive fire protection systems, active fire protection systems, and fire safety management. The problem is whether the safety of the fire hazard in the existing low-income residential multi-story building is still fulfilled or not. In this paper, the study on performance bases fire protection in the low-income residential multi-story building in Surakarta city, Indonesia, namely Rusunawa A, will be presented. This building has a height of 5 floors, with a semi-double-loaded building mass with a vacuum in the middle. The existing condition of the building indicates that an active fire protection system in the form of a fire pump system for a fire hydrant system is damaged due to corrosion of the pipes caused by salt or corrosive water. The performance of the building fire safety studies by simulating Available Safety Egress Time (ASET) and Required Safety Egress Time (RSET). Both of these simulations were carried out to get the minimum level of fire protection that must be provided so that the building still meets the minimum requirements for safety. ASET simulations use Thunderhead Pyrosim software and RSET simulations using Thunderhead Pathfinder software. From the results of this study, we can estimate the potential for fire hazards, the time of growth of fire hazards, the time needed for evacuation of residents, and the results of evaluating compliance with existing conditions and additional fire protection proposals needed to overcome the lack of existing conditions.Keywords: Fire survey; Fire modeling; Multi-story residential building; Performance-based fire protection; Simulation